(untitled) (MAUSAM, 1985)
Weibull and x2 distributions were fitted to three years wind speed data of jessore meteorological station. The values of the parameters to both the distributions were calculated for each month. It was found that the monthly mean wind speed and the available energy were fairly reproduced by both the distributions.